Applications and comparison of quadratic and cubic rational Bezier curve on batik design / Muhammad Izhar Ishak - Ishak, Muhammad Izhar (2017)
Rational Bezier curve is well known areas of research in computer aided geometric design (CAGD). This research proposed a new method to develop Batik design which is quadratic and cubic rational Bezier curve. This is a new approach of for the Batik industry by implementing the method using Mathematica software. This research deals with generating the Batik design and manipulation of weight magnitude to generate design closest to the real figure. This research is to improve Batik industry by using computer aided geometric design in generating a design. Lastly the results show that this research has potential to improve the Batik industry.